The forgotten prophet : Bishop Henry Mcneal Turner and the African American prophetic tradition - Johnson, Andre E. (Lexington Books, 2012)
The Forgotten Prophet: Bishop Henry McNeal Turner and the African American Prophetic Tradition, by Andre E. Johnson, is a study of the prophetic rhetoric of 19th century African Methodist Episcopal Church bishop Henry McNeal Turner. By locating Turner within the African American prophetic tradition, Johnson examines how Bishop Turner adopted a prophetic persona. As one of America's earliest black activists and social reformers, Bishop Turner made an indelible mark in American history and left behind an enduring social influence through his speeches, writings, and prophetic addresses. This text offers a definition of prophetic rhetoric and examines the existing genres of prophetic discourse, suggesting that there are other types of prophetic rhetorics, especially within the African American prophetic tradition. In examining these modes of discourses from 1866-1895, this study further examines how Turner's rhetoric shifted over time. It examines how Turner found a voice to article not only his views and positions, but also in the prophetic tradition, the views of people he claimed to represent. The Forgotten Prophet is a significant contribution to the study of Bishop Turner and the African American prophetic tradition.